ANALISIS KEMAMPUAN KONEKSI MATEMATIS SISWA DITINJAU DARI PENGGUNAKAN MODEL PEMBELAJARAN CORE (CONNECTING, ORGANIZING, REFLECTING, EXTENDING) - Nina Anriani Pulungan; Nunik Ardiana; Muhammad Syahril Harahap (JURNAL MathEdu (Mathematic Education Journal), 2021)
The aim of this study is to analyze students’ mathematical connection ability on the topic of Phytagoras theorem which reviewed on using CORE learning model at the eighth grade students of SMP Negeri 8 Padangsidimpuan. The research was conducted by applying experimental method (intact group comparison design) with 54 students as the sample and they were taken by using Cluster random sampling technique. Sample was divided into two groups, 27 students as control class (using lecture) and 27 students as experimental class (using CORE). Based on descriptive analysis, it was found: (a) the average of students’ mathematical connection ability before using lecture learning model was 50.82 (fair category) and after using lecture learning model was 73.66 (enough category) and (b) the average of students’ mathematical connection ability before using CORE learning model was 50.72 (fair category) and after using CORE learning model was 85.25 (good category). Furthermore, based on inferential statistic by using N-Gain, the result showed g= 0.369 (low category) for control class and g=0.706 (high category) for experimental class. It ‘s concluded that using CORE more effective than lecture learning model on the topic of Phytagoras theorem at the eighth grade students of SMP Negeri 8 Padangsidimpuan.